NiCo Nanorod Array Supported on Copper Foam as a High-Performance Catalyst for Hydrogen Production From Ammonia Borane - Li, Liling; Guo, Binshan; Li, Hang; Zhang, Xibin; Feng, Yufa; Liao, Jinyun (Frontiers in Materials, 2021)
Searching for inexpensive, durable, and active catalysts for the dehydrogenation of ammonia borane (AB) is an important subject in the field of hydrogen energy. In this study, we have fabricated NiCo nanorod arrays anchored on copper foam (CF) by a simple hydrothermal process. The catalytic performance of those array catalysts in AB hydrolysis was studied. It was found that NiCo-1/CF showed the highest catalytic activity with a hydrogen generation rate (HGR) of 1.03 Lhydrogen g-1 min-1, which was much higher than that for the unsupported NiCo-1 catalyst. It has been demonstrated that strong base can significantly enhance the hydrogen production. After six catalytic cycles, the morphology, crystal structure, and catalytic activity were maintained, indicating the NiCo-1/CF sample showed good reusability and high durability. Considering their low cost and high performance, the NiCo nanorod arrays anchored on CF can be a strong candidate catalyst for hydrogen generation for mobile hydrogen-oxygen fuel cells.